Local Culture-Based Marketing Strategy: A Study of Companies in the Archipelago - Sandi, Eric Krisna (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2025)
Local culture-based marketing is increasingly becoming an important strategy for companies operating in the Indonesian archipelago, a region rich in cultural diversity and traditions. This article explores how companies in the Indonesian archipelago are adopting and implementing local culture-based marketing strategies to enhance their appeal and connect with consumers. This research uses a case study approach to several companies that have successfully integrated local culture elements into their marketing strategies. Key findings suggest that local culture-based marketing not only strengthens brand identity but also enhances customer loyalty by creating strong emotional resonance. However, these companies also face challenges in balancing globalization and locality, and ensuring that local culture approaches are applied authentically and sensitively. This article suggests that a deep understanding of local culture and active engagement with the community can be key to success in a culture-based marketing strategy.